10 - Ideologies, Governance and the Public Sphere in Cameroon - Aseh, Nfamewih (Africa Development, 2021)
The founding history of Cameroon, as a nation-state was influenced by externally imposed factors, which also means that the founding political philosophy on which the neo-colonial state in Cameroon rests is traceable to foreign sources. Hence, Cameroon has no indigenous philosophical basis of existence from which an indigenous worldview should have emerged with its religion, literature, paintings, music, etc., to govern a public sphere that derives from and supports its own reality. And since the ‘Idea of Kamerun’ was transformed into a neo-colonial political structure during the Cold War for the purpose of achieving a foreign economic objective, like the original idea itself, one of the ways of achieving that desired goal was by dominating the public sphere with idiomatic expressions that claim to make life rather than being supportive of reality, which at the same time sought to destroy the foundation of all indigenous political philosophies, yet with no intention of establishing a universal ideal. The hypothesis of this article is that for the foreign founding philosophy to be maintained and reproduced in the public domain for the survival of the foreign-oriented kleptocratic state, there was the need to flood the public sphere with ideological mechanisms of public mediation for the effective epistemic control of the population. The result is the emergence of a fractured and contested public sphere that selectively ‘favours’ certain social categories for the success of the project of domination. This article, which seeks to develop a theory that explains the operation of the public sphere in a neo-colonial context, will thus examine, from a historical standpoint, the origins of a selected sample of some of the idiomatic expressions that govern the public sphere in Cameroon and the ideological options they represent, as a methodological preference to showing their correlation with the project of domination. The aim is to show how governance is mediated by the alienating role of an incoherent public sphere – dominated by representations of foreign ideologies – which does not seek to create a common consciousness in all citizens but rather to help maintain and perpetuate a fractured image of the Enlightenment. This is reinforced by a style of governance that thrives on a fractured public sphere, an understanding of which should illustrate a public sphere that encourages hybridised notions that are critical for foreign interference, meddling, destruction and domination within the overall project of ‘nation building’. The article also aims at showing the role of trans-territorial influences in the ‘development’ of the public sphere in Cameroon and how this has been changing over the years.